지방간 모델에서 가시오가피 발효물의 간 기능 개선 효과 - 조주현(Ju-Hyun Cho); 박인재(In-Jae Park); 최수영(Soo-Young Choi); 백순옥(Soon-Ok Baik); 김충식(Choong-Sik Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
We demonstrated that Acanthopanax senticosus fermentation products (FM-5111 and FM-5131) administered to rats functionally protect against DL-ethionine-induced and ethanol-induced fatty liver models. In DL-ethionine-induced fatty liver models, the serum concentrations of aspartate aminotransferase (AST), as well as liver concentrations of triglyceride and total lipid against the control decreased in FM-5111 and FM-5131 treated rats. In ethanol-induced fatty liver models, FM-5111 and FM-5131 treated rats showed a decrease in the liver concentrations of triglyceride and total lipid in ethanol-induced fatty liver models. There were no significant differences in the serum concentrations of AST and alanine aminotransferase in FM-5111 and FM-5131 treated rats. Additionally, FM-5111-, or FM-5131-treated rats showed no significant differences in the body weight gain between the control. These results indicate that Acanthopanax senticosus fermentation products might have protective effects against DL-ethionine-induced and ethanol-induced fatty liver models. 본 연구에서는 두 종류의 가시오가피 발효물 추출물(FM-5111, FM-5131)에 대한 지방간 예방 및 개선 효능을 검토하였다. 그 결과 FM-5111, FM-5131 모두 ethionine과 ethanol 지방간 모델에서 간 손상의 지표인 AST의 수치를 감소시키며, 간 내 총 지질량과 중성지방 함유량을 감소시키는 효능을 보이고 있다. 특히 간 내 총 지질량과 중성지방 함유량의 감소 정도로 보았을 때, ethanol 지방간 모델에서 더욱 두드러진 효능을 보이고 있다. 따라서 FM-5111과 FM-5131은 비알코올성 지방간 형성을 예방하고 알코올에 의해 형성된 지방간을 개선하는 효능을 가지고 있으며, 비알코올성 지방간과 알코올성 지방간 모델에서 간 손상 등을 억제하는 것으로 판단된다.